2016
DOI: 10.1016/j.fuel.2016.05.104
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conversion of lignin to phenols: Relevance between chemical structure and pyrolysis behaviors

Abstract: In this study, the Fourier transform infrared (FTIR) spectrometry and the 13 C-1 H correlation two-dimensional (2D) heteronuclear single-quantum coherence (HSQC) nuclear magnetic resonance (NMR) were introduced to determine the chemical structure of soda alkali lignin (SAL) and Alcell organosolv lignin (AOL), and the relevance between chemical structure and pyrolysis behaviors was evaluated by thermogravimetric analysis (TGA) and pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). Results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 241 publications
(98 citation statements)
references
References 36 publications
6
92
0
Order By: Relevance
“…1 and summarized in Tab. S1 in the Supporting Information, typical absorptions of lignin structure were clearly recognized, including O-H stretching vibration (peak 1), C-H stretching vibration in methyl and methylene groups (peaks 2 and 3), aromatic skeletal vibrations (peaks 4, 5, and 7), and aromatic ring breathing (peak 8) [29]. In addition, peak 9 (1042 cm -1 ) and peak 10 (652 cm -1 ) were assigned to the absorptions of S-O bonds [30,31], which benefited from the sulfonic groups.…”
Section: Properties Of Calcium Lignosulfonatementioning
confidence: 99%
See 1 more Smart Citation
“…1 and summarized in Tab. S1 in the Supporting Information, typical absorptions of lignin structure were clearly recognized, including O-H stretching vibration (peak 1), C-H stretching vibration in methyl and methylene groups (peaks 2 and 3), aromatic skeletal vibrations (peaks 4, 5, and 7), and aromatic ring breathing (peak 8) [29]. In addition, peak 9 (1042 cm -1 ) and peak 10 (652 cm -1 ) were assigned to the absorptions of S-O bonds [30,31], which benefited from the sulfonic groups.…”
Section: Properties Of Calcium Lignosulfonatementioning
confidence: 99%
“…This suggested that the neutral-alkaline condition was more favorable as compared to acid condition. Lignin is composed of three typical building units: p-hydroxyphenyl (H), guaiacyl (G), and syringyl (S) units [12,29,38]. Therefore, these phenolic monomers degraded from lignin under subcritical condition had the three different aromatic units.…”
Section: Phenolic Compounds Enhanced By Metal Ion Catalystsmentioning
confidence: 99%
“…Pyrolysis is viewed as one of the most promising thermochemical technologies for lignin utilization [191,192]. The main compounds produced from lignin during fast pyrolysis are gaseous hydrocarbons (i.e., CO2, CO), volatile liquids (methanol, acetone and acetaldehyde), monolignols, monophenols (phenol, guaiacol, syringol, and catechol) and other monosubstituted phenols [188].…”
Section: Progress In Chemical Utilizationmentioning
confidence: 99%
“…(Pandey and Kim 2011;Wang et al 2013;Peng et al 2014;Liu et al 2016). However, the authors' previous research (Guo et al 2014(Guo et al , 2017 indicated that the phenols yields obtained from alkali lignin pyrolysis were approximately 60% liquid oil, while the solid product yield also reached 30%.…”
Section: Introductionmentioning
confidence: 98%